2000
DOI: 10.1287/mnsc.46.4.467.12058
|View full text |Cite
|
Sign up to set email alerts
|

Price Protection in the Personal Computer Industry

Abstract: P rice protection is a commonly used practice between manufacturers and retailers in the personal computer (PC) industry, motivated by drastic declines of product values during the product life cycle. It is a form of rebate given by the manufacturer to the retailer for units unsold at the retailer when the price drops during the product life cycle. It is a controversial policy in the PC industry because it is not clear how such a policy benefits the supply chain and its participants. We show that price protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(65 citation statements)
references
References 11 publications
0
60
0
Order By: Relevance
“…They showed that channel coordination is achieved by choosing the price protection credit properly in the single buying opportunity model. However, they don't discuss the issue win-win [23]. Lineh and Hong study channel coordination with revenue sharing contract for a two period newsboy problem between a single retailer and a single wholesaler.…”
Section: Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that channel coordination is achieved by choosing the price protection credit properly in the single buying opportunity model. However, they don't discuss the issue win-win [23]. Lineh and Hong study channel coordination with revenue sharing contract for a two period newsboy problem between a single retailer and a single wholesaler.…”
Section: Related Researchmentioning
confidence: 99%
“…The two-period newsboy problem setting discussed in this paper resembles the one describes in lee [23]. In this model, supply chain consists of a supplier and a single retailer, who supplier produces a product and sells it through a retailer ) R ( .…”
Section: A Model Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other extensions of the research have dealt with such issues as sharing of information, rebate policies, revenue sharing policies, e-commerce, price protection/rebates, and competition in the supply chain. Among the papers that cite this research are: Tsay (1990), Donohue (2000), and Cachon and Lariviere (2001)-dealing with information sharing; Taylor (2002) and Lee et al (2000)-dealing with rebate policies; Dana and Spier (2001), Pasternack (2002), and Cachon and Lariviere (2005)-dealing with revenue-sharing policies; Choi et al (2004)dealing with e-commerce; Lee et al (2000), Taylor (2001), and Taylor (2002)-dealing with price protection/rebates; Padmanabhan and Png (1997), Cachon and Zipkin (1999), and Mantrala and Raman (1999)dealing with competition in the supply chain.…”
Section: Academic Literaturementioning
confidence: 99%
“…Moreover, in time-based competition today, the unit cost of a high-tech product declines significantly over its short product life cycle. For example, the cost of a personal computer drops constantly as shown in Lee et al [1]. Therefore, using the EPQ formulation in stages other than the maturity stage or for a product with short product life cycle will cause varying magnitudes of error.…”
Section: Introductionmentioning
confidence: 99%